การพัฒนาเครื่องมือวัดประสบการณ์การเผชิญเหตุการณ์รบกวนใจ สำหรับนักเรียนชั้นมัธยมศึกษา - นวพรรษ เชื้อต่าย (จุฬาลงกรณ์มหาวิทยาลัย, 2015)
The purposes of this research were to construct the small t trauma measured instruments for secondary school students that classify to 3 groups including high, moderate and low small t trauma level and for study about small t trauma in secondary school students. The 660 samples were computed from the number of items in questionnaire for factor analysis using a stratified random sampling method. The instrument was the small t trauma measure for secondary school students which was created and developed by the researcher and verified by 5 experts in psychiatry and psychology. Furthermore, Data was analyzed by using the index of item objective congruence(IOC) for the content validity, factor analysis for construct validity, Cronbach’s alpha for reliability, t-test for discrimination, and using the percentile for cut of point. Then one-way ANOVA was administered to classify the small t trauma of secondary school students to high, moderate and low level. The data from samples was analyzed by using the descriptive statistic, t-test, one-way ANOVA and Chi – square test. The result showed that the small t trauma measured instruments were composed of 60 items which showed in the content validity, 56 items in construct validity and 59 items in discrimination(from 60 items). The total for Cronbach’s alpha reliability measure was .936. The cut of point were low(percentile ≤50th), moderate(percentile 51th-74th) and high(percentile ≥75th). Then one way ANOVA was administered to classify to high, moderate, and low level with the .01 level of significance. For study about small t trauma in secondary school students, the result showed that in the 660 samples, 50.1%, 26.0% and 23.9% were low, high, and moderate level of small t trauma respectively. Moreover, associated factors with small t trauma were gender and marital status of parent of student (Chi-square; p= .006 and .019).